Egyptology : search for the tomb of Osiris, being the journal of Miss Emily Sands, November 1926- - Andrew, Ian, 1962-; Harris, Nick, 1958-; Ward, Helen, 1962- (Cambridge, Mass. : Candlewick Press, 2004)
Purports to be the journal of Emily Sands during her travels in Egypt in 1926 to find the lost tomb of Osiris. Based on real Egyptology, each chapter covers a different place in Egypt.
Includes mummy cloth touch and feel patch, lift-the-flap map and illustrations, a folded "Farncombe Papyrus," an "Understanding Hieroglyphs" booklet (6 p. ; 9 cm.), Senet Egyptian game pieces and rules, and postcards.
1180
Accelerated Reader AR
Keywords: Osiris (Egyptian deity) -- Juvenile literature; Sands, Emily (Fictitious character) -- Diaries; Tombs -- Egypt -- Juvenile literature; Toy and movable books; Osiris (Egyptian deity); Tombs -- Egypt; Egypt -- Antiquities -- Juvenile literature; Egypt -- Antiquities